Pouchitis and ileal pouch disorders : a multidisciplinary approach for diagnosis and management - Shen, Bo (Academic Press, 2018)
Pouchitis and Ileal Pouch Disorders: A Multidisciplinary Approach for Diagnosis and Management provides much needed information on the evolution of pouch surgery, pouch surgery techniques, and surgery-associated complications, including inflammatory, functional, neoplastic, and metabolic complications. The book provides information on the anatomy of the pouch, pathogenesis of pouchitis and other pouch disorders, proper diagnostic modalities, and medical, endoscopic and surgical options for those disorders. The information has been compiled from a panel of national and international leading experts in the field, including basic scientists, gastrointestinal (GI) pathologists, GI radiologists, gastroenterologists, and more.